Uncovering a unique path: Antidromic AVRT utilizing a left anteroseptal Mahaim‐like accessory pathway. Issue 1 (25th August 2020) - Sandhu, Amneet; Tzou, Wendy S.; Borne, Ryan T.; Zipse, Matthew M.; Nguyen, Duy T.; Sauer, William H.
Abstract: A 40‐year‐old man presented to our emergency department 2 hours after onset of shortness of breath, palpitations, and presyncope secondary to an adenosine‐responsive wide complex tachycardia. Electrophysiology study was diagnostic for antidromic atrioventricular (AV) reentrant tachycardia utilizing a muscular connection from the anterior interventricular vein to the left ventricle with Mahaim‐like properties, successfully treated with ablation in the distal coronary sinus (CS) system. This case highlights accessory pathways (a) with unique features (i.e., Mahaim‐like characteristics) and (b) involving musculature from the distal CS system, thereby limiting the value of endocardial ablation for durable treatment. Importantly, the coronary venous system is an accessible vascular network for evaluation and catheter ablation of such arrhythmias.